European energy and climate policy requires ambitious targets for 2030 - Claudia Kemfert; Christian von Hirschhausen; Casimir Lorenz (DIW Economic Bulletin, 2014)
In January 2014, the European Commission proposed a framework for its climate and energy policy up to 2030. It includes targets for reducing greenhouse gases and using renewable energies, but no specific targets for increasing energy efficiency. By 2030, greenhouse gas emissions are to be reduced by 40 percent over 1990 figures. Another element of the proposal is the introduction of a market stability reserve for the European Emissions Trading Scheme. However, its impact would be too late and too weak. In regard to renewable energy use, the Commission has proposed a goal to achieve a share of 27 percent of gross final energy consumption throughout Europe. This appears unambitious against the background of developments to date. In addition, there is no mandatory division of these goals among the individual member states. The Commission's calculations are based on implausible technical and economic assumptions in the power sector. The estimated costs for nuclear power are too low, and it is assumed there will be a breakthrough in carbon capture technologies that seems unlikely from today's perspective. In contrast, cost assumptions in the field of renewable energies remain too high and outdated. In light of previous experience, specific goals for 2030 are required on three levels: greenhouse gas emissions reductions, renewable energies, and energy efficiency. According to the Commission's impact assessment, energy system costs would hardly increase even with more ambitious objectives. In addition, creating an appropriate framework would also enable positive developments in investment, exports, and employment. The German federal government should continue its commitment to an ambitious European policy to reduce greenhouse gas emissions, to increase the use of renewable energies, and to boost energy efficiency.
Keywords: Q43; Q47; Q48; Q54; 330; Europe; energy; climate; policy; 2030